(untitled) (Bangladesh Journal of Zoology, 2015)
The study on the morphology of Bengal eyed turtle, Morenia petersi (Anderson, 1879) was made between January 1997 and December 2000 in Narayanganj, Chandpur, Manikganj, Dhaka and Madaripur Districts of Bangladesh. The mean weight of adult male was 640.6 ± 165.4 g and of female 794.5 ± 194.89 g. The length and width of carapace as well as those of the plastron and the height of the shell varied with the body weight of the turtle. The percentage of hard parts of the body weight of M. petersi was 35.9 ± 1.3% and soft parts was 64.3 ± 1.2%, respectively. Bangladesh J. Zool. 42(1): 57-66, 2014